A new look at 9-substituted acridines with various biological activities - Kozurkova, Maria; Sabolova, Danica; Kristian, Pavol (Journal of applied toxicology, 2021)
Heterocycles have long been the focus of intensive study in attempts to develop novel therapeutic compounds, and acridine, a polynuclear nitrogen molecule containing a heterocycle, has attracted a considerable amount of scientific attention. Acridine derivatives have been studied in detail and have been found to possess multitarget properties, which inhibit topoisomerase enzymes that regulate topological changes in DNA and interfere with the essential biological function of DNA. This article describes some recent advancements in the field of new 9-substituted acridine heterocyclic agents and describes both the structure and the structure-activity relationship of the most promising molecules. The article will also present the IC50 values of the novel derivatives against various human cancer cell lines. The mini review also investigates the topoisomerase inhibition and antibacterial and antimalarial activity of these polycyclic aromatic derivatives.
Keywords: Tumor Cells, Cultured; inhibitory topoisomerasy II; vztahy mezi strukturou a aktivitou; Humans; Structure-Activity Relationship; 9-substituted acridine; Topoisomerase II Inhibitors; antimalarial; Antineoplastic Agents; antibakteriální látky; protinádorové látky; Acridines; anticancer; akridiny; nádorové buňky kultivované; antimalarika; antibacterial; lidé; Anti-Bacterial Agents; topoisomerase II inhibition activity; Antimalarials